As regras do jogo no cenário imobiliário Brasileiro – análise histórica das repercussões do setor de construção habitacional nos anos de 1964 a 2011 - políticas públicas instituídas, com ênfase na lei 10.931/2004 - Marco Túlio Pinto Dias (2017)
The objective of this study is to demonstrate how the different institutional configurations and macroeconomic environment affected the real estate sector and the built environment in the period between 1964 and 2011, focusing on institutions´ rules of the game, on the perspective of Douglas North´s neoinstitutionalist theory. It presents a historical analysis of the behavior of the real estate sector between the military period and the president Lula´s government and, as the market oscillated in cycles of retraction and expansion, driven by opportunism – prime consideration of institutional interests. It also presents public policies used as an instrument for regulating the social economical order, with emphasis on the implementation of Law 10.931 / 2004 – Lei de Patrimônio de Afetação.